Dormancy and awakening of cancer cells: the extracellular vesicle-mediated cross-talk between Dr. Jekill and Mr. Hyde - D’Antonio, Concetta; Liguori, Giovanna L. (Frontiers in Immunology, 2024)
Cancer cell dormancy is a reversible process whereby cancer cells enter a quiescent state characterized by cell cycle arrest, inhibition of cell migration and invasion, and increased chemoresistance. Because of its reversibility and resistance to treatment, dormancy is a key process to study, monitor, and interfere with, in order to prevent tumor recurrence and metastasis and improve the prognosis of cancer patients. However, to achieve this goal, further studies are needed to elucidate the mechanisms underlying this complex and dynamic dual process.Here, we review the contribution of extracellular vesicles (EVs) to the regulation of cancer cell dormancy/awakening, focusing on the cross-talk between tumor and non-tumor cells in both the primary tumor and the (pre-)metastatic niche. Although EVs are recognized as key players in tumor progression and metastasis, as well as in tumor diagnostics and therapeutics, their role specifically in dormancy induction/escape is still largely elusive. We report on the most recent and promising results on this topic, focusing on the EV-associated nucleic acids involved. We highlight how EV studies could greatly contribute to the identification of dormancy signaling pathways and a dormancy/early awakening signature for the development of successful diagnostic/prognostic and therapeutic approaches.